Development Of Supplementary Learning Of Islamic Cultural History On The Theme Of Khulafaur Rasyidin For Students Of Class V MI - Selvi Sri Wahyuni; Hasbi Indra; Wido Supraha (Civilization Research: Journal of Islamic Studies, 2026)
The development of this learning supplement is motivated by the imbalance in the learning of Islamic Cultural History which tends to emphasize cognitive aspects, while affective and psychomotor aspects are less considered. The purpose of this research is to develop an interesting and easily accessible digital multimedia-based learning supplement, to improve historical understanding and build applicative attitudes and skills on the theme of Khulafaur Rasyidin. This research uses the Research and Development (R&D) method with the ADDIE model, including analysis, design, development, implementation, and evaluation. The validation was carried out by material, media, and language experts, and tested on three teachers and 22 students of class V of MI Al Huda Bogor. The results of the study show the need for more interactive and contextual supplements, with validation scores for material experts (92.8%), media (87.5%), and language (82.5%), all of which are categorized as good to excellent. This supplement was positively rated by teachers and students, demonstrating its effectiveness in supporting more balanced learning.